Pamali and Multiculturalism: Islamic Thought in Preserving the Rights of Cultural Customs in Banjar Society - Fithriani, Ahda; Faridah, Faridah; Syarqawi, Fitriana; Jahra, Pati Matu (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2024)
The research titled